Home Security System Based on Raspberry Pi and PIR Sensor Using WhatsApp Messenger - Patrick Kristo Prayogo; Legenda Prameswono Pratama; Devan Junesco (Journal of Global Engineering Research and Science, 2025)
Home security is a crucial factor for everyone to protect property and ensure the safety of their family. Along with technological advancements, home security systems have evolved from simple mechanisms to sophisticated devices integrated with the Internet of Things (IoT). One of the widely used technologies in such systems is the Raspberry Pi, a small, affordable, and flexible computer capable of controlling other devices through its General Purpose Input/Output (GPIO) pins. The Passive Infrared (PIR) sensor also plays a vital role in home security systems due to its ability to detect human movement by sensing changes in infrared radiation emitted by the human body. By utilizing PIR sensors, security systems can detect motion inside or around the house, potentially indicating threats such as burglary attempts. In addition, fast and efficient communication is essential in security systems. WhatsApp Messenger, as one of the most popular instant messaging applications, offers convenience in sending alerts or notifications directly to the user’s device. The integration of Raspberry Pi, PIR sensors, and WhatsApp Messenger can create a home security system that is not only cost- effective but also capable of delivering real-time notifications to homeowners. By combining Raspberry Pi and PIR sensors with WhatsApp as a communication medium, the system offers advantages in cost, ease of installation, and efficiency in delivering alerts without requiring additional complex hardware. Therefore, this research aims to design and implement a Raspberry Pi and PIR sensor-based home security system with notifications sent via WhatsApp Messenger.